Teaching and teacher education in international contexts : ISATT 40th anniversary yearbook - Craig, Cheryl J.; Mena, Juanjo; Kane, Ruth G. (Emerald Publishing Limited, 2023)
Research on teacher education and classroom teaching has evolved significantly in recent decades, with more research taking an international or intersectional lens. The International Study Association on Teachers and Teaching (ISATT) has moved with the field, beginning as a predominantly white European and North American organization in 1983, it now has active membership from more than 60 countries across the globe. The ISATT 40th Anniversary Yearbook, presented over three volumes, reflects this growth through celebrating the contributions of ISATT members over time and offering current scholarly research to inform current and future teacher education and teaching. Bringing together top research from Emerald, Elsevier and Taylor & Francis published over the past 10 years, plus cutting-edge new chapters, Teaching and Teacher Education in International Contexts explores the growing global scope of research on teaching. The sections investigate the history of ISATT; teacher education reform; school reform and support structures; partnerships; and preparing teacher educators. All three volumes that make up the ISATT 40th Anniversary Yearbook offer invaluable insights for teacher educators and educational researchers the world over, offering international perspectives from North America, Europe, South America, Asia, Africa, and Australasia.
Keywords: Teachers -- Training of.; Teaching.; Education -- Teaching / Methods & Strategies.; Teaching skills & techniques.; elektronické knihy; electronic books